Citizens Safety and Enviromental Crime (Kriminalističke teme, 2006)
The problems concerning environmental protection, which are numerous and from day to day more complex, have imposed a large number of protective measures in the field of environmental protection. An adequate security level in the field of environmental protection was achieved by many regulations of which, considering their repressive capacity, criminal law norms are the most important since violation of those norms can endanger the environment in the most serious way. The most dangerous forms of social pathology involve environmental crime. And environmental crime is just one of the most serious crime forms that is very difficult to be detected and proved. However, it is a social reality. Environmental crime in the countries in transition made good use of conflicts and postconflict situation and has established some kind of original predator system. Environmental security as a basic social value was realized only then individual safety had been endangered because of low awareness of security and environment. The problems concerning environmental protection and environmental crime were neglected. However, almost every person, as an individual, must be aware of the importance and the role of the environment for the present generations to grow and to make progress but also he or she has to be aware of the obligation to protect and to save the environment for the next generations.